Neoadjuvant therapy improves outcomes in locally advanced signet-ring-cell containing esophagogastric adenocarcinomas - Heger, Ulrike; Peters, Leila; Nienhüser, Henrik; Blank, Susanne; Hinz, Ulf; Haag, Georg Martin; Ott, Katja; Ulrich, Alexis; Büchler, Markus W.; Schmidt, Thomas (Annals of surgical oncology, 2018)
BackgroundOnly a few studies have analyzed multimodal treatment concepts in the subgroup of signet-ring-cell containing upper gastrointestinal (GI) cancer. Recent retrospective, multicentric data favor primary resection without neoadjuvant chemotherapy for gastric signet-ring-cell containing carcinomas (SRCs). We compared the outcomes of primarily resected carcinomas with neoadjuvantly treated, locally advanced esophagogastric SRCs.MethodsA total of 310 patients with esophagogastric SRC-staged cT3/4/Nany/Many from a prospective unicentric database were included in this study; 192 (61.9%) received neoadjuvant therapy (NEO group) and 118 (38.1%) were primarily resected (RES group).ResultsOverall, 128 (41.3%) patients presented with adenocarcinoma of the esophagogastric junction (AEG) and 182 (58.7%) presented with gastric cancer. Neoadjuvant therapy was significantly associated with resection in curative intent (NEO: 91.1%; RES: 75.4%; P = 0.001), improved (y)pT category (P = 0.035), improved (y)pN category (P < 0.001), and R0 resections (curative intent cohort: 76.0% in NEO vs. 60.7% in RES; P = 0.010), among others, but not with postoperative complications. Overall survival was significantly improved by neoadjuvant treatment {median survival 28.5 months (95% confidence interval [CI] 14.4-39.6) vs. RES: 14.9 months (10.6-17.5); P < 0.001}, as well as in subgroups (AEG and gastric tumors, R0-resected patients, and patients with and without relevant comorbidities). Independent prognostic factors were neoadjuvant therapy (hazard ratio [HR] 0.66; P = 0.023), pT4 category (HR 1.71; P = 0.041), pN2 category (HR 1.86; P = 0.013), pN3 category (HR 2.40; P < 0.001), pM1 category (HR 1.95; P = 0.003), age > 70 years (HR 1.79; P = 0.006), gastric localization (HR 0.69; P = 0.032), American Society of Anesthesiologists classification 3/4 (HR 1.71; P = 0.004), and incomplete resection R1/2 (HR 1.6; P = 0.014).ConclusionsOur results demonstrate a survival advantage for advanced-stage esophagogastric SRC patients by neoadjuvant treatment.
Gesehen am 23.10.2019